Virtual environments and synchronous interactive collaborative work in the EBR, during the COVID-19 pandemic in Tacna - Gómez Janampa, Luzmila del Rosario (2023)
In 2020, as a result of the COVID-19 pandemic, the Ministry of Education (MINEDU) suspended school work using virtual classes. From this, the teachers of public and private institutions used different strategies for the development of their learning sessions as a means, so that different virtual environments were applied and they faced the main challenge of synchronous interactive collaborative work, through Information and Communication Technologies (ICT). In this context, an investigation was carried out that aimed to describe how virtual environments were used to carry out synchronous interactive collaborative work among regular basic education students in Tacna. Through a qualitative methodology based on interviews, the difficulty in achieving synchronous interactive collaborative work between student-student was evidenced, in contrast to teacher-student collaboration. Likewise, digital inequality was observed among the students of said institution, since the virtual environments did not reach 100% of the student population.